2015
DOI: 10.1007/s10608-015-9695-3
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Shared and Unique Features of Self-Concept Content and Structure in Borderline Personality Disorder and Depression

Abstract: Abstract:A number of clinical theories emphasise self-concept disturbance as central to borderline personality disorder (BPD). To date, however, there has been limited empirical examination of exactly how BPD changes the content and structure of selfconcept. Moreover, it is unclear if patterns of self-concept disturbance are unique to BPD or are driven by axis-I comorbidities such as depression. To examine this issue, the present study adopted a dimensional design, examining how performance on a novel adaptati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…The term self-concept is increasingly more important within the field of personality, both from an affective and an emotional perspective [1,2]. To analyse this psychological variable, it is very interesting to return to the basic cognitive processes of childhood, as they undergo a great evolution after the age of 6 until the end of adolescence [3].…”
Section: Introductionmentioning
confidence: 99%
“…The term self-concept is increasingly more important within the field of personality, both from an affective and an emotional perspective [1,2]. To analyse this psychological variable, it is very interesting to return to the basic cognitive processes of childhood, as they undergo a great evolution after the age of 6 until the end of adolescence [3].…”
Section: Introductionmentioning
confidence: 99%
“…A valenced dot probe task will be used to measure attentional bias to positive versus negative material (VDP) [100]. The Psychological Distance Scaling Task (PDST) [101, 102] will be used to measure positive versus negative schema organisation. The Probabilistic Selection Task (PST) [103] will be used to measure how quickly participants learn from positive versus negative reinforcement contingencies.…”
Section: Methodsmentioning
confidence: 99%
“…Studies using self-report questionnaires have typically found that BPD patients have more difficulty than controls in maintaining selfother boundaries (Beeney et al, 2015(Beeney et al, , 2016. Furthermore, their self-concept has been found to be more fragmented and less consistent over time than that of controls (Beeney et al, 2016;Evans et al, 2015;Vater et al, 2015). However, these studies do not directly address problems with SOD, but rather experiences of fragmentation and a lack of consistency in the representation of the self.…”
mentioning
confidence: 99%